2020
DOI: 10.3390/metabo10040127
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acid Profile and its Changes in Response to Cefoperazone Treatment in MR1 Deficient Mice

Abstract: Mucosal associated invariant T-cells (MAIT cells) are activated following recognition of bacterial antigens (riboflavin intermediates) presented on major histocompatibility complex class I-related molecule (MR1). Our previous study showed that MR1−/− knock-out (KO) mice (lacking MAIT cells) harbor a unique microbiota that is resistant to antibiotic disruption and Clostridioides difficile colonization. While we have characterized the microbiota of this mouse strain, changes in global metabolic activity in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…These were reflected by the intestinal metabolome changes, specifically, decreases in secondary bile acids, glucose, free fatty acids, and dipeptides, whereas increases in primary bile acids and sugar alcohols were also reported [ 15 ]. Our previous study showed similar results, where increases in primary bile acids and decreases in secondary bile acids were observed in mice after Cef administration [ 17 ]. Another study also showed that decreases in many host-gut microbiota co-metabolites (indole- and phenyl-containing metabolites, amino acids, vitamins, nucleotides, and bile acids) were observed in the urine from mice treated with penicillin (an antibiotic used to treat Gram-positive bacterial infections) [ 18 ].…”
Section: Introductionsupporting
confidence: 70%
“…These were reflected by the intestinal metabolome changes, specifically, decreases in secondary bile acids, glucose, free fatty acids, and dipeptides, whereas increases in primary bile acids and sugar alcohols were also reported [ 15 ]. Our previous study showed similar results, where increases in primary bile acids and decreases in secondary bile acids were observed in mice after Cef administration [ 17 ]. Another study also showed that decreases in many host-gut microbiota co-metabolites (indole- and phenyl-containing metabolites, amino acids, vitamins, nucleotides, and bile acids) were observed in the urine from mice treated with penicillin (an antibiotic used to treat Gram-positive bacterial infections) [ 18 ].…”
Section: Introductionsupporting
confidence: 70%
“…Antibiotics in general can indirectly impact host metabolism, immunity, the nervous system, and other key aspects of normal physiology through their influence on the diversity and function of microbial communities ( Clemente et al, 2012 ; Cryan et al, 2020 ; Rooks and Garrett, 2016 ; Tang et al, 2019 ). Cefoperazone has been well-studied in C57BL/6 J mice, where it decreases the abundance of bacterial taxa that numerically dominate the gut of untreated animals ( Firmicutes and Bacteroides ) ( Reeves et al, 2011 ); decreases the total bacterial load in the gut by ∼3 orders of magnitude ( Antonopoulos et al, 2009 ); significantly alters bile acid levels and composition ( Sun et al, 2020 ; Theriot et al, 2016 ); and opens niches for opportunistic pathogens like Clostridioides difficile ( Jenior et al, 2018 ) and Candida albicans ( Antonopoulos et al, 2009 ; Gutierrez et al, 2020 ). We hypothesized that the combination of gut microbiome perturbation and arsenic would be detrimental compared to mice treated with either antibiotic or arsenic alone, and while this was certainly the case, we did not necessarily expect to observe such interindividual variability in host response and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary bile acids can act in multiple ways as signaling molecules, through activation of the nuclear Farnesoid X receptor (FXR), vitamin D receptor, and through surface expressed GPCRs. The spectrum and distribution of gut bile acids and their derivatives depends, to a large extent, on the composition of the microbiome [ 121 ]. Engagement of these compounds in many physiological aspects has been appreciated for some time, but a role for bile acids as controllers of the Treg–Th17 axis has emerged only recently.…”
Section: Tryptophan Metabolitesmentioning
confidence: 99%